MODELAGEM DE GESTÃO EMPREENDEDORA DE QUALIDADE, SEGURANÇA, MEIO AMBIENTE E SAÚDE QSMS: A EXPERIÊNCIA DA PLATAFORMA P-54 - França, Celeste Maria de Freitas (2009)
The need of application of methodologies and project tools, the need of interaction of different competences is more and more a demand of the companies on the part of the market that has his/her work process consolidated progressively, for the new technologies, globalization of products and production processes. Inside of this context he/she interferes the integrated modality of project recruiting, for packages of Engineering, Suppliers and Construction-usually denominated hire EPC (Engineering, Procurement and Constrution) that comes as a modality with capacity to assist to the demands of the contracting parties. In this sense, the central objective of this dissertation is to present an approach of the Gestão QSMS, ruled in the Study of Case of the Plataforma P-54, looking for to structure a rising of information that allows a diagnosis on the processes of planning of the EPCistas , in the touching the subjects affect to the discipline QSMS. As result hopes to present an analysis of the strategic methodology of the enterprising administration with focus in the interfaces of the processes, technology and people among contracted and contracting party.